The Influence of Screen Time and Nutrition Knowledge on Dietary Habits Among Nutrition Students - Fadilla Chairunnisa Fitri; Atikah Adyas; Adhi Nurhartanto (CV. CENDIKIA JENIUS INDONESIA, 2025)
The increasingly digital lifestyle among university students has the potential to influence dietary behavior, even among those with good nutrition knowledge. This study is important to evaluate the extent to which screen time and nutritional knowledge are associated with dietary habits among nutrition students. The aim of this research was to determine the relationship between screen time and nutrition knowledge with food consumption habits among students of the Nutrition Study Program at Mitra Indonesia University. This quantitative study used a cross-sectional design involving 71 students selected through purposive sampling. Data were collected using questionnaires in May 2025 and analyzed using the chi-square test. The results showed that most respondents had high screen time (98.6%), moderate nutritional knowledge (57.7%), and poor dietary habits (47.9%). Statistical analysis revealed no significant relationship between screen time (p=0.323) or nutritional knowledge (p=0.133) and dietary habits. In conclusion, neither nutrition knowledge nor screen time duration sufficiently influences healthy eating behaviors among students. Recommended Behavior-based interventions and more practical nutrition education strategies are needed to improve dietary patterns in the digital age.